O reconhecimento da receita para fins de Imposto sobre a Renda da Pessoa Jurídica (IRPJ) - Baltazar, Rafael Luiz da Silva (2023)
The object of this study is to investigate the recognition of revenue for purposes of the Corporate Income Tax (IRP J), which implies the taxation of the legal entity for the calculation of the tax due. The revenue concept is applied to distinguish between gross revenue and net revenue. Financial income, in turn, was not addressed due to methodological reasons. From the Brazilian Federal Constitution of 1988, especially the tax on income and earnings of any nature, its definition was extracted: the tax must occur from equity increases in a certain period. Then, the research focuses on the IR Matrix rule tax of incidence to address the legal relationships established through the conditions and types of contracts (typical and atypical). As an example, the most common ones are used, such as purchase and sale, barter, and forward sale, and, as a complement, two types assets: NFTs (non-fungible tokens) and court-ordered payments. The first (NFTs) was chosen due to the difficulty of monitoring the legislation harming technological development; the second (court-ordered payments), due to the limited dissemination of their studies. Finally, court judgments on the recognition of revenue in the IPPJ are analyzed. In six chapters, including the Introduction and Conclusion of the work, the dissertation was built based on qualitative scientific research (whose collected data provide details and depth of knowledge for a better understanding of the revealed implications), of an exploratory nature (its emphasis is on the subjective character of the object and in the study of its particularities through literature review), and guided by the analyticaldescriptive narrative